Penerapan Sistem Perjanjian Kerja Waktu Tertentu Dalam Perspektif Hukum Positif Indonesia - Ilela, Yudith; Laturette, Adonia Ivonne; Kuahaty, Sarah Selfina (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Indonesia, as a country under the rule of law, upholds the principle of equality before the law. This principle is also applied in the freedom to contract, which requires a valid agreement to meet four conditions: agreement, competency, specific object, and lawful cause. The Fixed-Term Employment Agreement is a form of employment relationship between employers and workers that suffers from shortcomings in its implementation. Many employers do not understand the rules, leading to deviations in practice.Purposes of the Research:  The aim of this research is to examine and analyze the implementation of the Fixed-Term Employment Agreement system from the perspective of positive law in Indonesia.Methods of the Research: This research is a normative juridical research, using a descriptive analytical research type using primary, secondary and tertiary legal sources. The approach used is a statutory approach (Statute Approach) and conceptual approach (conceptual approach). The technique of collecting legal materials uses a literature study which is then analyzed qualitatively in order to answer the problems studied.Results of the Research: Based on the research results, it is shown that the protection of workers in Fixed-Term Employment Agreements  is not optimal in its implementation due to frequent violations. This is attributed to the unclear regulations regarding the application of The Fixed-Term Employment Agreement, particularly concerning types of work that are one-time, temporary, seasonal, or related to new products. Furthermore, the lack of government supervision in the The Fixed-Term Employment Agreement creation process enables employers to easily violate regulations without legal repercussions.